2016
DOI: 10.1103/physreve.93.023206
|View full text |Cite
|
Sign up to set email alerts
|

Weakly nonlinear ion-acoustic excitations in a relativistic model for dense quantum plasma

Abstract: The dynamics of linear and nonlinear ionic-scale electrostatic excitations propagating in a magnetized relativistic quantum plasma is studied. A quantum-hydrodynamic model is adopted and degenerate statistics for the electrons is taken into account. The dispersion properties of linear ion acoustic waves are examined in detail. A modified characteristic charge screening length and "sound speed" are introduced, for relativistic quantum plasmas. By employing the reductive perturbation technique, a Zakharov-Kuznet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…8,39 Various relevant theoretical investigations have been proposed, predicting excitations that are yet to be detected. 17,[42][43][44] Considering the possibility for experimental confirmation (realization) of our predictions in the laboratory, we note that the present model becomes relevant for ultra-high densities, when both degeneracy and relativistic effects come into play. For instance, an one-dimensional density n 0 % 10 11 m À1 , corresponding to n 0 % 0:1 (and a 3D equivalent of n 3D % 10 33 m À3 ), is not at all inconceivable in view of the already available laser-plasma compression technology.…”
Section: Discussionmentioning
confidence: 51%
“…8,39 Various relevant theoretical investigations have been proposed, predicting excitations that are yet to be detected. 17,[42][43][44] Considering the possibility for experimental confirmation (realization) of our predictions in the laboratory, we note that the present model becomes relevant for ultra-high densities, when both degeneracy and relativistic effects come into play. For instance, an one-dimensional density n 0 % 10 11 m À1 , corresponding to n 0 % 0:1 (and a 3D equivalent of n 3D % 10 33 m À3 ), is not at all inconceivable in view of the already available laser-plasma compression technology.…”
Section: Discussionmentioning
confidence: 51%
“…Figure 3 shows a density plot for the oblique collision of the two soliton solutions in Eqs. (34) and (35) where the impact of is clear in the two panels of Fig. 3.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 93%
“…We consider a two component degenerate relativistic plasma composed of ions and electrons. Introducing the normalized set of governing equations that were adopted from 34 as follows: …”
Section: The Hydrodynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…and highlighted the possible application regarding from the view point of laboratory and space plasma [33]. ElShamy et al studied the non-linear solitary wave propagation in dense degenerate magneto plasma and they concluded that ion cyclotron frequency, direction cosine of wave vector has a great impact on the propagation of solitary wave in such plasma [34].…”
Section: Introductionmentioning
confidence: 99%